Simulated reconstruction of soil water distribution and isotope fractionation under the influence of AMF inoculation - Yinli BI; Lexuan TIAN; Zengming KE (Meitan kexue jishu, 2023)
Water resources determine the vegetation structure and types in the ecological restoration process, and are the main limiting factor for achieving green production and ecological restoration in mining areas. To investigate the effects of inoculation of Arbuscular Mycorrhiza Fungi (AMF) on plant root water extraction, simulated soil water distribution and water isotope fractionation in a semi-arid coal mining area, this study conducted the indoor stratified soil column simulation experiment with maize as the test plant. Three treatments were set up as pure soil column (CK1), soil column + maize (CK2), and soil column + inoculated maize (AMF), with three replicates for each treatment. Meanwhile, the height of capillary water rise in soil columns, soil water content, as well as hydrogen and oxygen isotopes of maize stem water and soil water were measured. The growth and development of maize, water transport patterns, and discrepancies in soil water isotope fractionation at different depths among different treatments were also analyzed in this article. Results showed that: (1) Inoculation could effectively promote the growth and development of maize, with plant height, aboveground biomass, underground biomass and total root length increased by 15.8%, 23.4%, 43.4% and 21.0%, respectively, compared to CK2 treatment. (2) AMF have also promoted the root system to absorb the retain water in the bottom clay layer, increased the capillary water elevation by 18.9%, and expanded the water absorption space of maize by approximately 50%, thereby affecting the water distribution in the soil columns. (3) There were significant fractionation differences between the surface and deep soil water of soil column compared to the initial water. At the surface layer of 0 ~ 10 cm, the 18O and 2H enrichment coefficients of CK2 and AMF treatments were significantly lower than those of CK1 treatment, while at the deep layer of 60 ~ 70 cm, the 18O and 2H enrichment coefficients of AMF treatment were significantly higher than those of CK2 treatment, indicating that AMF could enhance the phenomenon of isotopic fractionation in deep subsoil water. In summary, inoculation can improve the absorption of deep soil water by maize in the reconstructed soil layer, prompt the root system to counter-release to the upper dry soil through the water lifting effect, improve the water redistribution capacity, and affect the soil water isotope fractionation at different depths. The results could provide scientific basis and technical support for addressing the shortage of water resources for land reclamation in semi-arid coal mining areas.